Generation and Characterization of Temperature Resistant Mutant of Recombinant PJ156/CAV-17 Virus - ANDI UTAMA; HIROYUKI SHIMIZU (Microbiology Indonesia, 2007)
Previous study revealed that a recombinant virus between poliovirus (isolate PJ156) and coxsackie A virus serotype 17 (CAV-17), namely PJ156/CAV-17, was temperature sensitive. It is well known that two amino acids in 3D region (His-73 and Ile-362) are determinants for temperature sensitivity of poliovirus, in particular for Sabin 1 strain. However, it is not known whether those amino acids affect the temperature sensitivity for other enteroviruses. Sequence analysis of 3D region of PJ156/CAV-17 showed that amino acid in 3D-73 and -362 were Tyr and Ile, respectively, similar with the sequence of parental CAV-17 virus. Since amino acid in 3D-73 of PJ156/ CAV-17 was not His, it is suggested that the temperature sensitivity of the PJ156/CAV-17 was associated with the Ile-362. To confirm this suggestion, the temperature-sensitive escape mutants of PJ156/CAV-17 were generated by blind passaging at 39.5 oC. The escape mutants were then recovered and plaque purified, and the sequence of 3D region was determined. It was found that the amino acid in 3D-362 was Thr, instead of Ile. Consequently, Ile- 362 was proved to be involved in temperature sensitivity of PJ156/CAV-17. Full sequences of both viruses were also determined and compared. Furthermore, the characteristics of the temperature resistant of PJ156/CAV-17 variant were analyzed. It is confirmed that the recovered PJ156/CAV-17 virus could grow well at 39.5 oC, and there was strong correlation between temperature sensitivity and attenuation.